Enteric fever in Children at Dhulikhel Hospital - Singh, Srijana Dongol; Shrestha, Shreema; Shrestha, Narayan; Manandhar, Sanjay (Journal of Nepal Paediatric Society, 2013)
Introduction: Typhoid fever is one of the most common public health problems in Nepal. It occurs in all parts of the world where water supplies and sanitation are sub-standard. In Dhulikhel hospital, this is one of the top acute febrile illnesses in inpatient department. The objectives of this study were to evaluate the clinical and laboratory parameters including culture and sensitivity, the response to therapy, and complications of enteric fever among child cases at Dhulikhel Hospital. Materials and Methods: This retrospective study was conducted at Dhulikhel Hospital, Kathmandu University Teaching Hospital from January 2009 to June 2011. Statistical analysis was done with SPSS. Results: There were total of 138 cases of enteric fever admitted. There were 73 (53%) male and 65 (47%) female. Eighty-one percent were above five years of age. The most common clinical presentation was fever (100%) followed by headache and G I symptoms. Hepatomegaly was the most common sign seen among the cases and was seen in 110cases (79.71%). Most of the patients had normal WBC count 100 (72.46%) Widal test was positive in 70 (50.72%) cases and blood culture was positive in 52(37.68%) cases. Nalidixic acid was found to be resistant in 26 (50%) cases. Complications were seen in only 7 (5%) enteric fever cases. Conclusion: Typhoid fever is predominant in school going children in Nepal with slight male predominance. Fever lasting over 3 days followed by headache and GI symptoms are the major presenting symptoms. In making the diagnosis, the isolation of bacteria from blood is the “gold standard”. Nalidixic acid resistant Salmonella typhi is on the increasing trend. Pneumonia was found to be the most common complication among all other complications seen in enteric cases. In Dhulikhel Hospital this is one of the top acute febrile illnesses in inpatient department. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6682 J. Nepal Paediatr. SocVol.32(3) 2012 216-220